MyD88-dependent Toll-like receptor 2 signaling modulates macrophage activation on lysate-adsorbed Teflon™ AF surfaces in an in vitro biomaterial host response model - McKiel, Laura A.; Ballantyne, Laurel L.; Negri, Gian Luca; Woodhouse, Kimberly A.; Fitzpatrick, Lindsay E. (Frontiers in Immunology, 2023)
The adsorbed protein layer on an implanted biomaterial surface is known to mediate downstream cell-material interactions that drive the host response. While the adsorption of plasma-derived proteins has been studied extensively, the adsorption of damage-associated molecular patterns (DAMPs) derived from damaged cells and matrix surrounding the implant remains poorly understood. Previously, our group developed a DAMP-adsorption model in which 3T3 fibroblast lysates were used as a complex source of cell-derived DAMPs and we demonstrated that biomaterials with adsorbed lysate potently activated RAW-Blue macrophages via Toll-like receptor 2 (TLR2). In the present study, we characterized the response of mouse bone marrow derived macrophages (BMDM) from wildtype (WT), TLR2-/-and MyD88-/-mice on Teflon™ AF surfaces pre-adsorbed with 10% plasma or lysate-spiked plasma (10% w/w total protein from 3T3 fibroblast lysate) for 24 hours. WT BMDM cultured on adsorbates derived from 10% lysate in plasma had significantly higher gene and protein expression of IL-1b, IL-6, TNF-a, IL-10, RANTES/CCL5 and CXCL1/KC, compared to 10% plasma-adsorbed surfaces. Furthermore, the upregulation of pro-inflammatory cytokine and chemokine expression in the 10% lysate in plasma condition was attenuated in TLR2-/- and MyD88-/-BMDM. Proteomic analysis of the adsorbed protein layers showed that even this relatively small addition of lysate-derived proteins within plasma (10% w/w) caused a significant change to the adsorbed protein profile. The 10% plasma condition had fibrinogen, albumin, apolipoproteins, complement, and fibronectin among the top 25 most abundant proteins. While proteins layers generated from 10% lysate in plasma retained fibrinogen and fibronectin among the 2 This is a provisional file, not the final typeset article top 25 proteins, there was a disproportionate increase in intracellular proteins, including histones, tubulins, actins, and vimentin. Furthermore, we identified 7 DAMPs or DAMP-related proteins enriched in the 10% plasma condition (fibrinogen, apolipoproteins), compared to 39 DAMPs enriched in the 10% lysate in plasma condition, including high mobility group box 1 and histones. Together, these findings indicate that DAMPs and other intracellular proteins readily adsorb to biomaterial surfaces in competition with plasma proteins, and that adsorbed DAMPs induce an inflammatory response in adherent macrophages that is mediated by the MyD88-dependent TLR2 signaling pathway.